2009
DOI: 10.1128/jvi.00189-09
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structures of Chikungunya and Venezuelan Equine Encephalitis Virus nsP3 Macro Domains Define a Conserved Adenosine Binding Pocket

Abstract: Macro domains (also called"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
278
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(293 citation statements)
references
References 51 publications
14
278
0
1
Order By: Relevance
“…It was noteworthy that the good scoring phytochemicals bind to the conserved aspartic acid (D10).Some phytochemicals used hydrogen bond to interact with D10 while others had non-bonded interactions. This single aspartic acid, conserved through all macro domains is responsible for the specific binding of the adenine base (Malet et al, 2009).The affinity between the receptor and the substrate may get disturbed due to this strong binding. The DockScore of the ligands showed that the receptor-ligand interaction energy and the ligand internal energy were in the most favorable range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noteworthy that the good scoring phytochemicals bind to the conserved aspartic acid (D10).Some phytochemicals used hydrogen bond to interact with D10 while others had non-bonded interactions. This single aspartic acid, conserved through all macro domains is responsible for the specific binding of the adenine base (Malet et al, 2009).The affinity between the receptor and the substrate may get disturbed due to this strong binding. The DockScore of the ligands showed that the receptor-ligand interaction energy and the ligand internal energy were in the most favorable range.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of Chikungunya virus nsP3 macro domain that defines a conserved adenosine binding pocket (3GPO) was considered as the target of the study (Malet et al, 2009). It was retrieved from the Protein Data Bank (Berman et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The ribose and pyrophosphate group fit well into the pocket formed by the two loop regions (G314-N316 and G223-G224). As a result, the macro domain specifically recognizes the terminal ADP-ribose moiety of the poly-ADP-ribose chain [21][22][23] (Fig. S10B).…”
Section: Comparison With the Adp-ribose Binding Modes Of Other Recognmentioning
confidence: 99%
“…We recently determined the crystal structures of macro domain from the Chikungunya virus (CHIKV) and the Venezuelan Equine Encephalitis virus (VEEV) at 1.65 A and 2.30 A resolution respectively by single crystal X-ray diffraction. These macro domains are active as adenosine di-phosphoribose 1 00 -phosphate phosphatases [16]. Despite significant effort good quality single crystals of the MAYV nsP3 macro domain were not available whereas crystallization trials resulted in reproducible microcrystalline samples, mainly needles as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%